Jehoshaphat and His Prayer among Sixteenth-Century Lutherans - Haemig, Mary Jane (2004)
Martin Luther, writing in his Betbuchlein in 1522, declared:Among the many harmful books and doctrines which are misleading and deceiving Christians and give rise to countless false beliefs, I regard the personal prayer books as by no means the least objectionable. They drub into the minds of simple people such a wretched counting up of sins and going to confession, such un-Christian tomfoolery about prayers to God and his saints! Moreover, these books are puffed up with promises of indulgences. … These books need a basic and thorough reformation if not total extermination.… But I just don't have the time to undertake such a reformation; it is too much for me alone.